Paraguay : Sixth and Final Review Under the Stand-By Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the Sixth and Final Review Under the Stand-By Arrangement for Paraguay. The program remains broadly on track. All performance criteria for end-March 2008 were met, and those for end-June 2008 are expected to have been observed. With one exception, all structural benchmarks for 2008 are expected to be implemented, albeit with delays. The economy grew 6 3/4 percent in 2007 and is expected to continue expanding at least 5 percent in 2008 driven by strong agricultural exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet